Roles, Functions, and Mechanisms of Long Non-coding RNAs in Cancer - Fang, Yiwen (2016)
Long non-coding RNAs (lncRNAs) play important roles in cancer. They are involved in chromatin remodeling, as well as transcriptional and post-transcriptional regulation, through a variety of chromatin-based mechanisms and via cross-talk with other RNA species. lncRNAs can function as decoys, scaffolds, and enhancer RNAs. This review summarizes the characteristics of lncRNAs, including their roles, functions, and working mechanisms, describes methods for identifying and annotating lncRNAs, and discusses future opportunities for lncRNA-based therapies using antisense oligonucleotides.